2020
DOI: 10.1186/s12891-020-03608-4
|View full text |Cite
|
Sign up to set email alerts
|

A rare case report of laryngopharyngeal polyp formation following anterior cervical discectomy and fusion (ACDF)

Abstract: Background Anterior Cervical Discectomy and Fusion (ACDF) has been regarded as the “gold standard” treatment of cervical spondylosis. Though it has good outcomes, many complications still exist, such as loss of fixation, degeneration of adjacent segments, dysphagia and pharyngeal perforation. In view of current literature, this study is the first to report a case of laryngopharyngeal polyp following ACDF. Case presentation A 63 year old male patient suffered from cervical spine hyperextension after trauma ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The clinical manifestations of tracheal injury can be nonspecific and may include coughing, dyspnea, laryngopharyngeal polyp, subcutaneous emphysema, pneumomediastinum, and even acute respiratory failure [ 3 , 5 , 6 ]. This report actually demonstrated that patients with tracheal perforation could be asymptomatic and therefore diagnosis might be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of tracheal injury can be nonspecific and may include coughing, dyspnea, laryngopharyngeal polyp, subcutaneous emphysema, pneumomediastinum, and even acute respiratory failure [ 3 , 5 , 6 ]. This report actually demonstrated that patients with tracheal perforation could be asymptomatic and therefore diagnosis might be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Many complications may occur during the cervical spine surgery due to the complex anatomical structure of the neck and the wide range of involved areas, such as soft tissue injury, loss of xator, degeneration of adjacent segments, dysphagia, pharyngeal perforation, throat polyps, etc, and even intraoperative spinal cord displacement, expansion, nerve spinal cord injury and others, making it unfavourable to the postoperative recovery of spinal nerve function [3] . In addition, processes such as tracheal intubation, posture, spinal decompression can also lead to secondary cervical injury, thus causing iatrogenic injury.…”
Section: Introductionmentioning
confidence: 99%